Factors Influencing The Export Demand For Mangosteen (Garcinia Mangostana): - Hidayat, Rifki Tsani; Fitriadi, Budhi Wahyu; Jakiyah, Ulpah (CV. Utami, 2025)
The agricultural sector is a vital pillar of the Indonesian economy, including through the export of high-value horticultural commodities such as mangosteen (Garcinia mangostana). Indonesia, particularly West Java, is a major mangosteen producer, with China serving as the largest destination market due to the increasing demand for quality tropical fruit. Despite substantial export opportunities, mangosteen export performance is influenced by global economic factors such as international prices, exchange rates, and the purchasing power of destination countries, as reflected in Gross Domestic Product (GDP). This study aims to analyze the factors influencing demand for Indonesian mangosteen exports to China for the 2015–2024 period. The method used is multiple linear regression analysis with the independent variables being mangosteen prices, the Rupiah/Yuan exchange rate, and China's GDP. Data were obtained from Statistics Indonesia (BPS), the Ministry of Trade, and other international institutions. The results show that all three variables have a significant simultaneous effect. Partially, prices and China's GDP have a significant positive effect, while the exchange rate has a significant negative effect. These findings emphasize the importance of price stability and strengthening trade relations to increase Indonesian mangosteen exports.